2004
DOI: 10.1093/sleep/27.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness Combined with Low Alcohol Intake in Women Drivers: Greater Impairment but Better Perception than Men?

Abstract: Legally "safe" BAC markedly worsen sleepiness-impaired driving in women. However, they seem to be aware of their impaired driving and are able to judge the degree of risk entailed. Such an attitude may contribute to the lower incidence of sleep- or alcohol-related crashes in women compared with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…[40] Other studies have found that the combination of alcohol (BAC = .04) and restricted sleep increased lane drifting during simulated driving. [41,42] These studies suggest that lower BACs combined with other impairment sources can have a similar effect on driving as BACs that are above the per se limit. The prevalence of fatal crashes where alcohol and another drug were found underestimates the comorbidity weakness of per se definitions.…”
Section: Figure 4-2 Alcohol and Drug Co-morbiditymentioning
confidence: 94%
“…[40] Other studies have found that the combination of alcohol (BAC = .04) and restricted sleep increased lane drifting during simulated driving. [41,42] These studies suggest that lower BACs combined with other impairment sources can have a similar effect on driving as BACs that are above the per se limit. The prevalence of fatal crashes where alcohol and another drug were found underestimates the comorbidity weakness of per se definitions.…”
Section: Figure 4-2 Alcohol and Drug Co-morbiditymentioning
confidence: 94%
“…This is described in detail elsewhere (Barrett et al, 2004). Briefly, it comprises an immobile car with an interactive full size computer-generated dull, monotonous roadway.…”
Section: Simulatormentioning
confidence: 99%
“…Increases in alpha and theta power indicate increasing sleepiness (Rechtschaffen and Kales, 1968;Å kerstedt and Gillberg, 1990). The EEG power in this (4-11 Hz) range was averaged per minute, and standardized for each participant using the method described by Barrett et al (2004).…”
Section: Eeg and Eogmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the intake of drugs, sleep deprivation in itself is considered a risk factor for road traffic accidents (Anund 2009;Barrett et al 2004;Biggs et al 2007;Desai et al 2006;Hack et al 2001;Jackson et al 2008;Lenne et al 1998;Orzel-Gryglewska 2010;Philip et al 1999Philip et al , 2004Reynolds and Banks 2010;Vakulin et al 2007). Amphetamine influences the function of the central nervous system by releasing and blocking the reuptake of catecholamines and has been shown to improve cognitive and motor function in sleep-deprived subjects (Magill et al 2003).…”
Section: Introductionmentioning
confidence: 99%